2022
DOI: 10.3389/feduc.2022.991263
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of educational innovation culture by a Delphi expert panel

Abstract: This paper aims to reflect on educational innovation from the point of view of its representation as an indispensable element within the pedagogical culture of educational centers. We present the current elements that constitute the definition of educational innovation, its dimensions, obstacles, and determining factors that will delimit the institutionalization of the innovation process in education. To achieve this aim, we applied the Delphi technique and formulated questions whose answers were agreed upon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…It requires learning strategies derived from complex pedagogical skills in project-based learning, personalized learning, and the use of technology in the classroom to produce active, participatory, and relevant learning environments (Gilbert et al, 2021). Its components may vary according to the scenarios, where it is designed and implemented; however, various researchers (Gallardo-Córdova et al, 2029;López-Larios et al, 2022;Noor & Crossley, 2013;Parejo et al, 2022;Ramírez-Montoya, 2020) conclude that it consists of at least five essential elements:…”
Section: Educational Innovation and Skills Developmentmentioning
confidence: 99%
“…It requires learning strategies derived from complex pedagogical skills in project-based learning, personalized learning, and the use of technology in the classroom to produce active, participatory, and relevant learning environments (Gilbert et al, 2021). Its components may vary according to the scenarios, where it is designed and implemented; however, various researchers (Gallardo-Córdova et al, 2029;López-Larios et al, 2022;Noor & Crossley, 2013;Parejo et al, 2022;Ramírez-Montoya, 2020) conclude that it consists of at least five essential elements:…”
Section: Educational Innovation and Skills Developmentmentioning
confidence: 99%
“…The scientific foundations of this theory are disclosed in the works of Awais and Ameen (2019), Belayutham et al (2019), Veiga Ávila et al (2019), and Cockshut et al (2020. The issues of modernization of universities and their contribution to the innovative development of the higher education and science system are considered in the works of Goyal and Sergi (2015), Popkova and Zmiyak (2019), Batool (2022), Nguyễn et al (2022), Parejo et al (2022), andPrenger et al (2022). ccording to the above literature sources, innovative development of higher education is defined in this paper as the improvement of the position of the leading universities in international university rankings (e.g., the ranking QS) through an increase in R&D activity of universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on entrepreneurial management has been mainly related to the business sphere (Long et al, 2021;Ratten et al, 2021;Singh et al, 2022;Pallathadka et al, 2023) highlighting it as an essential element in the concretization of the actions raised, in the case of entrepreneurial management as a social entrepreneurship competence studies are scarce (Bonesso et al, 2018;Okolie et al, 2021;Cruz-Sandoval et al, 2022;Parejo et al, 2022;Romero and Nalangan, 2023) in particular, no studies were identified that relate entrepreneurial management to other variables that can explain the profile of social innovation in students, The literature on the subject highlights that entrepreneurial management is one of the elements in education to which less importance has been given and that this could have repercussions on the lack of confidence to undertake social entrepreneurship and thus to carry out actions that generate a social impact, so it is necessary to develop educational programs to promote entrepreneurial skills in the economic, social or technological fields (Ahmed et al, 2020;Jena, 2020;Aledo Ruiz, 2022).…”
Section: Introductionmentioning
confidence: 99%